(3GdOQI GdefXheIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s
(3ChdgG (B:s
(3Ef GdUdGI ef CaVd GdbQH(B***(3hCced GdWGYGJ WQG hCMHs
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO ef HGH (B((3GdJYRjI hSGFQ GdCMcGe hGddhGMb(B) (3bhdg(B: (3ef KdKgG cZjQgG hGdHPd(B***(3dYGOe GdLgGR ajg GdaVds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B113s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B740s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B461s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis